Developmental morphology and key genes involved in early flower development in Acacia mangium Willd - Ponniah, Komala (2003)
Flowering is an important aspect in the life cycle of higher plants, since it signifies the onset of sexual reproduction and the development of seed, grains and fruits. To forest plantations the development of these reproductive structures are a bane since it occurs at the expense of vegetative growth. In Malaysia, Acacia mangium which is an important forest plantation species flowers profusely and thus much of its photosynthate is converted to produce reproductive structures. This study was initiated to understand the genetic control of flower development in A. mangium with the ultimate aim of controlling this process towards our requirement. With the help of scanning electron microscopy and light microscopy, early flower development in A. mangium was documented. The emerging inflorescence primordium is double-protected by a thick piece of bud scale which in turn lies Flower meristems are formed only after the bracts have been laid down in a spiral pattern along the axis of the inflorescence. The sepals and petals are arranged in alternating pentamerous whorls. Sepals are initiated in a helical fashion in either direction, with the first sepal varying in position while petals are initiated simultaneously. Development along the axis is slightly staggered with flowers at the base being more advanced than flowers at the tip of the inflorescence, but prior to anthesis all flowers are synchronized developmentally. AML, the A. mangium equivalent of LEAFY (LFY), a floral meristem identity gene, was isolated from young inflorescences. AML is 77% identical to UNIFOLIATA (UNI), the homologue of LFY from pea. Its expression was detected mainly in shoot apical meristems (SAM) from mature flowering trees and young inflorescences. The AML gene is single copy in the A. mangium genome and has two introns. AAL, the A. auriculiformis equivalent of LFY is 98% identical to AML and 76% identical to UN!. Both AML and AAL formed a clade with UNI to represent the legumes in a phylogenetic tree constructed from various LFY homologues. Two MADS-box genes have also been cloned from A. mangium. AmMADSJ, the first MADS-box gene reported in a Mimosoideae was isolated from the SAM of mature flowering trees. AmMADSJ is very similar in sequence to BpMADS5 from silver birch with an identity of 63% and is expressed in all reproductive tissues including young pods with the highest expression in developing inflorescences. AmAfADSJ is also expressed in roots. Sequence analysis and phylogenetic analysis show that AmMADSl belongs to the SQUA subgroup of the MADS-box family of transcription factors.